Pendampingan Pengurusan NIB Dan PIRT Bagi UMKM Di Kelurahan Bendogerit, Kecamatan Sananwetan, Kota Blitar - Aldira Safira Hartono; Althafahreza Citra Zeptavio; Aulia Dwi Anggraeni; Dewi Puspa Arum; Febriyanti Mardhiyyah; Fikri Akmal Zain (Pusat Riset dan Inovasi Nasional, 2023)
Bendogerit Village is one of the villages in the Sananwetan sub-district, Blitar City. In its development, these MSMEs experience problems in licensing, such as the absence of a Business Identification Number (NIB). Student groups of 30 KKN-Thematic in this case provide assistance to MSMEs in making NIB through the Online Single Submission system. 20 UMKM intending to arrange NIB, but 8 UMKM are willing to make NIB. Mentoring and assistance activities in registering NIB and PIRT for MSMEs are very effective in increasing MSME business capabilities. Assistance and management assistance make the registration process easier and MSMEs more confident in doing so.